Manifesto Coding Instructions (Second Revised Edition) - Andrea Volkens (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
Since 1979, the Manifesto Research Group (MRG) has been collecting and coding election programs with the aim of estimating policy preferences of political parties. Detailed descriptions of this project can be found in Budge et al. (1987, 2001), Laver and Budge (1992), and Klingemann et al. (1994). During the first phase of the project, while the classification scheme was being developed, each group member was responsible for his or her own data collection. Reliability and validity of content analytic procedures had been secured through intensive group discussions. The second phase of the project started in 1989. In the context of its 'Comparative Manifestos Project' (CMP), the Social Science Research Centre Berlin (WZB) provided resources for updating and expanding the MRG data. Coders are now hired to do the content analysis according to this coding handbook. The handbook describes in detail how to select the documents, how to identify the coding units, and how to apply the classification scheme. A reliability test given in the handbook is used for training coders. – – Seit 1979 sammelt und analysiert die Manifesto Research Group (MRG) Wahlprogramme, um politische Positionen von Parteien komparativ zu messen. Detaillierte Darstellungen des Gesamtprojekts finden sich Budge et al. (1987, 2001), Laver and Budge (1992) und Klingemann et al. (1994). Während der ersten Phase des Projektes wurde das Klassifikationsschema entwickelt und jedes Mitglied der Gruppe brachte die Daten eines Landes in den komparativen Datensatz ein. Die zweite Phase des Projektes begann 1989 mit der Gründung der Abteilung 'Institutionen und sozialer Wandel' am Wissenschafts-zentrum Berlin für Sozialforschung (WZB). Seither stellt das WZB Ressourcen zur Verfü-gung, um die Datensammlung zu vervollständigen und zu erweitern. Die Inhaltsanalysen werden heute von Codern in den Heimatländern anhand des vorliegenden Handbuches vorgenommen. Das Handbuch führt die Coder umfassend in die Selektion der Programme, die Identifikation der Codiereinheiten und die Anwendung des Klassifikationsschemas ein. Ein dem Handbuch beigefügter Reliabilitätstest dient dem Codertraining.
Keywords: 300